Mesozoic crustal growth in Mainland Southeast Asia: Zircon U-Pb and Hf isotopic evidence from the Late Cretaceous Luyingtang granitic pluton in the northernmost SE Asian granite Province, SW China. (1st April 2020) - Cong, Feng; Li, Wen-Chang; Wu, Fu-Yuan; Huang, Liang; Huang, Xiao-Ming; Sun, Jie; Liu, Xiao-Chi; Hu, Fang-Yang; Hu, Shi-Xue; Wu, Guang-Hui
Graphical abstract: Highlights: The Luyingtang granites are of I-type affinity and emplaced at 70–83 Ma. The granites contain a significant proportion of juvenile component. The hinterland I-type granites formed by melting of mixed sources. Basaltic underplating is an important mechanism in crustal growth of Southeast Asia. Abstract: The Changning-Menglian suture in the Sanjiang region of SW China, the Chiang Rai line in Thailand, and the Bentong-Raub suture in Peninsular Malaysia are marked by remnants of the Paleo-Tethys oceanic lithosphere in Mainland Southeast Asia. We present U-Pb ages and Hf isotopic compositions of zircon from Luyingtang granites east of the Changning-Menglian suture, with the aim of identifying their sources and petrogenesis, which are significant for understanding the crustal evolution of the Mainland Southeast Asia. The Luyingtang granitic pluton is located in the northernmost SE Asian granite Province, SW China. New zircon U-Pb ages indicate that the granites were emplaced in the Late Cretaceous, in accordance with the regional scale inland magmatic event in Mainland Southeast Asia. Petrographically, the samples range from granodiorite, biotite granite, two-mica granite to pegmatite. The biotite granite, two-mica granite and pegmatite have low contents of TiO2, Al2 O3, FeO*, MgO, CaO and P2 O5, but high values of SiO2 and K2 O, compared to the granodiorite. The granodiorite, biotite granite and two-mica granite invariably show enrichment in light rare earth elements (LREE). The biotite granite and two-mica granite show negative Eu anomalies, but the granodiorite displays weak Eu anomaly. The pegmatites show a clear tetrad effect and contain pronounced negative Eu anomalies. All the rocks demonstrate characteristic negative Nb, Ta, Sr and Ti anomalies, and a positive Pb anomaly, when plotted on spidergrams. Most of the granites are characterized by positive εHf ( t ) values (0.3–8) and fairly young TDM2 ages (612–1094 Ma), suggesting they contain a significant proportion of juvenile component. Hf isotopic modelling shows that the Luyingtang granites are likely to have been produced by partial melting of mixed sources, which were probably of basalts in proportions of 50–70% and Precambrian continental crust. The emplacement of granites with such a large proportion of mantle-derived component indicates crustal growth in Mainland Southeast Asia during Mesozoic. In contrast, one of the two-mica granite samples displays negative εHf ( t ) values (−7.6 to −3) and older TDM2 ages (1305–1599 Ma), which suggest a more crustal affinity. The arc-continent collision during the Cretaceous may have induced foundering of an over-thickened lithospheric mantle keel beneath the Paleo-Tethys orogenic belt, and then resulted to localized upwelling of asthenosphere mantle and basaltic underplating. The parental magmas of the hinterland I-type granites formed by melting of a mixed source, containing both Precambrian crust and mantle-derived basalt, followed by extensive magmatic differentiation.